MANAJEMEN SUMBERDAYA MANUSIA (SDM) PADA LEMBAGA PENDIDIKAN ISLAM DI MAN I TANAH JABO AYE ACEH UTARA - Nurhayati Nurhayati (AL-ILMU, 2023)
In improving the quality of educational resources that contribute to workforce development, the composition or arrangement, processes, maintenance or education, and the concentration of work relationships are crucial factors. However, Islamic principles in human resource management not only consider the interests of advancing institutions, schools, and organizations, but also focus on the needs of employees, learners, and the demands of the wider community. By integrating these aspects, work effectiveness can be achieved, and predetermined goals can be realized. Recognizing the importance of human resources in organizations or educational institutions as a challenge in achieving effective and efficient educational goals, the author is motivated to conduct research on human resource management in the Islamic educational institution, MAN I Tanah Jambo Aye, North Aceh Regency. The author formulates several problems related to human resource management in the Islamic educational institution, with a focus on improving the quality of employees and educational standards. This study adopts a qualitative research design, specifically field research, using data collection techniques such as interviews, observations, and documentation.The conclusion drawn from this research is that to enhance the quality of human resources, the school principal undertakes various activities such as assigning tasks, organizing workshops, and providing training tailored to the respective fields of the teachers. The aim is to develop the knowledge and skills possessed by the teachers, advance the educational institution, and encourage learners to expand their knowledge in the field of education. Keywords: Management, Human Resources, Islamic Educational Institution